Характеристика динаміки змін гемостазу, протеолізу, фібринолізу і ліпопероксидації у тканині нирок = Description of dynamics change hemostasis, proteolysis, fibrinolysis and lipid peroxidation in kidney tissue - R. M. Borys; V. M. Sirman; O. P. Nykytenko; W. Zukow; A. I. Gozhenko (Kazimierz Wielki University, 2016)
Borys R. M., Sirman V. M., Nykytenko O. P., Zukow W., Gozhenko A. I. Характеристика динаміки змін гемостазу, протеолізу, фібринолізу і ліпопероксидації у тканині нирок = Description of dynamics change hemostasis, proteolysis, fibrinolysis and lipid peroxidation in kidney tissue. Journal of Education, Health and Sport. 2016;6(3):241-258. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56064 http://ojs.ukw.edu.pl/index.php/johs/article/view/3615   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 20.03.2016. Accepted: 23.03.2016.   УДК: 616.61-008.9:616.151.5   ХАРАКТЕРИСТИКА ДИНАМІКИ ЗМІН ГЕМОСТАЗУ, ПРОТЕОЛІЗУ, ФІБРИНОЛІЗУ І ЛІПОПЕРОКСИДАЦІЇ У ТКАНИНІ НИРОК   Р. М. Борис, В. М. Сірман, О. П. Никитенко, В. Жуков, А. І. Гоженко   Український науково-дослідний інститут медицини транспорту МОЗ України, м. Одеса, Украина UMK w Toruniu Резюме Метою нашого дослідження було вивчити та проаналізувати динаміку змін гемостазу, протеолізу, фібринолізу і ліпопероксидації у тканині нирок при експериментальному перитоніті, а також  при ад'ювантному артриті Пірсона у щурів та визначення динаміки змін біохімічних показників, що характеризують основні патофізіологічні механізми клітинного і тканинного ураження нирок. Для вирішення поставлених задач проведені серії експериментів in vivo. У роботі використано 189 самців білих щурів з середньою масою тіла 0,193±0,018 кг. Дослідження проводили через 2, 4, 6 і 12 міс. після індукції ад'ювантного артриту Пірсона.  При експериментальному перитоніті, проведено 7 серій експериментів на 486 самцях білих щурів з масою тіла 0,17-0,30 кг. Встановлено, що при обох експериментальних моделях запалення виникають однотипні механізми гемостазу, протеолізу, фібрінолізу і ліпопероксидації у тканині органу.   Ключові слова: ураження нирок, протеоліз, фібриноліз, ліпопероксидація.   DESCRIPTION OF DYNAMICS CHANGE HEMOSTASIS, PROTEOLYSIS, FIBRINOLYSIS AND LIPID PEROXIDATION IN KIDNEY TISSUE   R. M. Borys, V. M. Sirman, O. P. Nykytenko, W. Zukow, A. I. Gozhenko   Ukrainian Scientific Research Institute of Transport Medicine, Ministry of Health of Ukraine UMK w Toruniu Resume The aim of our study was to examine and analyze the dynamics of changes in hemostasis, proteolysis, fibrinolysis and lipid peroxidation in kidney tissue in experimental peritonitis, as well as adjuvant arthritis in rats Pearson and determine dynamic changes of biochemical indicators of the basic pathophysiological mechanisms of cell and tissue damage to the kidneys . To solve this problem, a series of experiments in vivo. The paper used 189 male albino rats with an average body weight of 0,193 ± 0,018 kg. The study was conducted at 2, 4, 6 and 12 months. After induction of adjuvant arthritis Pearson. In experimental peritonitis, held 7 series of experiments on 486 white male rats weighing 0,17-0,30 kg. Found that in both experimental models of inflammation there are similar mechanisms of hemostasis, proteolysis, fibrinolysis and lipid peroxidation in the fabric body.   Keywords: kidney damage, proteolysis, fibrinolysis, lipid peroxidation.